Improving the Stability of Protein–Protein Interaction Assay FlimPIA Using a Thermostabilized Firefly Luciferase - Ohmuro-Matsuyama, Yuki; Gomi, Keiko; Shimoda, Takuya; Yamaji, Hideki; Ueda, Hiroshi (Frontiers in Bioengineering and Biotechnology, 2021)
The protein–protein interaction assay is a key technology in various fields, being applicable in drug screening as well as in diagnosis and inspection, wherein the stability of assays is important. In a previous study, we developed a unique protein–protein interaction assay “FlimPIA” based on the functional complementation of mutant firefly luciferases (Fluc). The catalytic step of Fluc was divided into two half steps: D-luciferin was adenylated in the first step, while adenylated luciferin was oxidized in the second step. We constructed two mutants of Fluc from Photinus pyralis (Ppy); one mutant named Donor is defective in the second half reaction, while the other mutant named Acceptor exhibited low activity in the first half reaction. To date, Ppy has been used in the system; however, its thermostability is low. In this study, to improve the stability of the system, we applied Fluc from thermostabilized Luciola lateralis to FlimPIA. We screened suitable mutants as probes for FlimPIA and obtained Acceptor and Donor candidates. We detected the interaction of FKBP12-FRB with FlimPIA using these candidates. Furthermore, after the incubation of the probes at 37°C for 1 h, the luminescence signal of the new system was 2.4-fold higher than that of the previous system, showing significant improvement in the stability of the assay.